An exploratory study of the economic and social problems of adjustment faced by Kampuchen refugees in an oil palm estate in Sepang, Selangor / Loo Choo Im - Loo , Choo Im (1986)
The problems that refugees face in adjusting to life in a new country have been studied in many countries. The resettlement of Kampuchean refugees in this country is a relatively new phenomenon and because it is new, not many studies have been done on it. This study attempts to explore some of the economic and social adjustment problems that some Kampuchean refugees in an oil palm estate in this country face. The estate where the study took place was the Selangor Oil Palm industries Corporation (SOPIC) Sdn. Bhd. Located in the district of Sepang, Selangor. Also investigated in this study are the attitudes and reactions of the local people who work and live in the same estate towards the Kampuchean refugees. This graduation exercise is divided into five chapters. In the first chapter, the objectives and methodology of the study are stated out in detail. The second chapter looks into the background of their situation in their former society and events that brought the refugees into Malaysia. The third chapter is concerned with their present socio-economic status to determine their level of socio-economic well-being. In the fourth chapter, their attitudes towards their life here and towards their interactions and attitudes of the local workers in the estate towards the Kampucheans. In the final chapter, the conclusions of the study are drawn.